Characterisation of the compatibility of isotactic polypropylene/poly(acrylonitrile-butadiene-styrene) (iPP/ABS) blends by aid of dynamic rheological responses. (7th June 2021) - Liu, Jingru; Pan, Yingtong
ABSTRACT: Dynamic rheology, phase morphology and mechanical properties of isotactic polypropylene/poly(acrylonitrile-butadiene-styrene) (iPP/ABS) blends containing various amounts of ABS were investigated. The results of small-amplitude oscillatory shear studies show that the complex viscosity and storage modulus of the blends display significant negative deviation from the linear mixing rule, which is related to the poor interfacial interaction between two components. This was justified by mechanical property measurements. All the blends have a two-phase morphology, indicating the immiscibility of the ABS and iPP. Clear co-continuous morphology for P60A40, P50A50, and P40A60 blends could be observed, with creep recoverable compliances showing maximum values. Dynamic rheological measurements (including small-amplitude oscillatory shear and creep-recovery) are sensitive tools to get insights into the compatibility and phase morphology in the polymer blends, as well as interfacial interaction in such systems.